(untitled) (Pakistan Business Review, 2022)
With the growing footmark of Chinese MNCs around the globe, the management of the host country employees has been a new challenge on the horizon. The study aims to understand the human resource management and cross-cultural practices and challenges faced by Chinese companies across the border. This cross-sectional and exploratory study used semi-structured interviews and focus groups for the data collection. The respondents were Chinese managers from Chinese companies and Chinese cultural centres working in Pakistan. This study used thematic analysis with triangulation of sources and methods. This study found culture as a key theme affecting all the emerging human resource management themes. Chinese companies working in Pakistan use informal social networks in addition to traditional applicant recruitment methods. Cultural training is common along with technical training in particularly state-owned Chinese enterprises. Although in many Chinese companies, the parent country nationals fill top positions, local employees could be seen working in the top tier management of some Chinese companies. The Chinese companies’ management practices have not been paid much attention to in this region. This study enables us to develop deep insights into Chinese companies’ human resource management practices and challenges. This research also contributes to the literature on international human resource management and cross-cultural management.